The scorpion-tailed orb-weaving spiders (Araneae, Araneidae, Arachnura) in Australia and New Zealand - Castanheira, Pedro De S.; Didham, Raphael K.; Vink, Cor J.; Framenau, Volker W. (Zootaxa, 2019)
The scorpion-tailed orb-weaving spiders in the genus Arachnura Vinson, 1863 (Araneidae Clerck, 1757) are revised for Australia and New Zealand. Arachnura higginsii (L. Koch, 1872) only occurs in Australia and A. feredayi (L. Koch, 1872) only in New Zealand. A single female collected in south-eastern Queensland (Australia) is here tentatively identified as A. melanura Simon, 1867, but it is doubtful that this species has established in Australia. Two juveniles from northern Queensland do not conform to the diagnoses of any of the above species and are illustrated pending a more thorough revision of the genus in South-East Asia and the Pacific region. An unidentified female from Westport (New Zealand) does not conform to the diagnoses of A. feredayi and A. higginsii, but is not described due to its poor preservation status. Arachnura caudatella Roewer, 1942 (replacement name for Epeira caudata Bradley, 1876), originally described from Hall Sound (Papua New Guinea) and repeatedly catalogued for Australia, is considered a nomen dubium.